(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Obstructive jaundice (OJ) remains one of the most clinically significant challenges in hepatopancreatobiliary surgery. It develops primarily as a consequence of biliary obstruction caused by choledocholithiasis, benign biliary strictures, echinococcal cyst rupture into bile ducts, or inflammatory and congenital lesions of the biliary tract. Without timely intervention, OJ leads to progressive hepatic insufficiency, portal hypertension, septic cholangitis, and ultimately multi-organ failure. In Uzbekistan, the incidence of benign obstructive jaundice continues to rise, underscoring the need for refined diagnostic protocols and evidence-based minimally invasive treatment strategies.